Characteristics of gonadotropin response, follicular development, and endometrial growth and maturation across consecutive cycles of clomiphene citrate treatment - Opsahl, Michael S.; Robins, Edwin D.; O’Connor, Dennis M.; Scott, Richard T.; Fritz, Marc A. (Fertility and sterility, 1996)
To examine the patterns of gonadotropin response, follicular development, and endometrial growth and maturation across consecutive cycles of clomiphene citrate (CC) treatment. Prospective analysis of cycle characteristics. Academic tertiary medical center. Nineteen consenting anovulatory infertile women receiving standardized, cyclic, incremental treatment with CC (50 to 150 mg/d, cycle days 5 to 9) for ovulation induction. In each of up to six consecutive treatment cycles, urinary LH was monitored twice daily from cycle day 10 until detection of the LH surge or day 21; blood samples and transvaginal ultrasound (US) examination were obtained on cycle days 3, 10, and every 1 to 3 days thereafter until collapse of the dominant follicle. Endometrial biopsy was performed 11 to 13 days after the LH surge in the first, third, and sixth ovulatory cycle. Follicular phase duration, peak follicular diameter, the number of preovulatory follicles, and peak endometrial thickness and echo pattern remained consistent across consecutive ovulatory (n=55) and anovulatory (n=23) treatment cycles. Endometrial dating was ≥3 days out of phase in 2 of 31 (6%) cycles sampled. Peak serum E2 and P concentrations did not vary with cycle number or correlate with endometrial thickness or echo pattern. Cycle day 10 FSH levels were significantly higher in ovulatory subjects than in anovulatory subjects. Patterns of gonadotropin response, follicular development, and endometrial growth and maturation remain consistent across consecutive cycles of CC treatment.